Pengaruh Guru Pendidikan Agama Kristen Sebagai Pembimbing Terhadap Pembentukan Karakter Siswa kelas IV Dan V Parlondut Tahun Pembelajaran 2023/2024 - Renta Romiama Panjaitan; Nurelni Limbong; Goklas J Manalu (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The purpose of this research is to find out how much influence Christian Religious Education Teachers as Mentors have on the Character Formation of Class IV and V Parlondut Students for the 2023/2024 academic year. The research method used is a quantitative research method. The population is all students in class IV and V of Parlondut for the 2023/2024 academic year, namely 28 people and this research is a population study. Data was collected using a positive closed questionnaire with 40 items, namely 20 items for variable 0.05,n=28) = 0.374. b) Testing a significant relationship obtained a value of tcount= 3.364 > ttable(=0.05,dk=n-2=26)= 2.056. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂=